Optimization of Enteral Feeding for Acute Decompensated Congestive Cardiac Failure with Fluid Restriction - Abdul Jalil, Muhammad Hakim; Ab Hamid, Mohd Ramadan; Hamdan, Norhafizah; Mohd Rusli, Siti Farhanah (Jurnal Gizi dan Pangan, 2025)
The aim of this case report is to explore dietitian’s clinical decision-making in providing nutritional care. Ms. C, an 84-year-old Chinese woman with underlying atrial fibrillation, hypertension and diabetes mellitus was admitted into ward due to worsening progression of heart failure complicated with Upper Gastrointestinal Bleeding (UGIB), Community Acquired Pneumonia (CAP) and hypervolemic hyponatremia. Ms. C’s BMI was normal for elderly (27 kg/m2) with estimated weight and height of 70 kg and 160 cm respectively. Patient was hyperglycemic, hypertensive, and breathing under ventilatory support. Prior to admission, she complained of lethargy, difficulty of breathing and stomach pain. Patient was on fluid restriction of 500 ml/day in view of body fluid retention. Patient was on enteral feeding 3 hourly 6 times per day tolerating 100 ml of diabetic formula providing energy of 456 kcal/day and protein of 20 g/day. Inadequate enteral infusion related to physiological changes (fluid retention) requiring restricted fluid intake as evidenced by estimated energy intake of 456 kcal/day and protein intake of 20 g/day less than energy requirement of 1,400 kcal/day and protein requirement of 84 g/day. The goal was to provide adequate energy and protein concomitantly adhering to the fluid restriction and achieving good glycemic control. Modular protein was added to the diabetic formula. Ms. C was able to tolerate 100ml enteral feeding throughout hospital stay. Managing patient with multiple organ complications prove to be challenging. High-density formula is often used for fluid restriction patient however inappropriate for diabetic patient. Product unavailability in the hospital also limiting patient care. Clinical reasoning and clinical judgment were necessary to ensure prioritization of patient care.